A non-linear analysis of the longitudinal static stability of light, multi-engined aircraft - Eshelby, M. E. (Cranfield University, 1979)
The longitudinal handling qualities of light aircraft have traditionally been assessed in terms of the slope of the static stability trim curves. This method of assessment is simple in terms of analysis as well as being a relatively easy task for the pilot to perform. The theory is however based on a simple linearised model of . the aircraft'and omits, amongst other things, the effects of power. A comparison between the estimated and measured trim curves of a typical light aircraft shows that the linearised theory severely overestimates its static stability. A design based on the linear assumptions would be unlikely to comply with airworthiness requirements. In Part II the main omissions from the linearised model are considered individually and their effect on the trim curves found. In Part I the individual contributions from Part II are used to complete the full, non-linear, trim equations and these are solved in terms of elevator angle and incidence to trim, n and ä. The solution shows that the non-linear analysis provides a good simulation of the flight measured trim curve data thus verifying the methods of estimation developed in Part II. The trim curves are considered in terms of incidence and lift coefficient and show that assumption of a linear lift-incidence relationship may cause some misleading interpretations of the trim curves drawn in terms of lift coefficient.